Amantadine treatment is associated with improved consciousness in patients with non-traumatic brain injury - Ruehl, Lena; Kuramatsu, Joji; Sembill, Jochen; Kallmünzer, Bernd; Madzar, Dominik; Gerner, Stefan; Giede-Jeppe, Antje; Balk, Stefanie; Müller, Tamara; Jäger, Jakob; Schwab, Stefan; Huttner, Hagen; et al. (Journal of Neurology Neurosurgery and Psychiatry, 2022)
Objective This study determined the effect of amantadine treatment on consciousness in patients with non-traumatic brain injury. Methods We pooled individual patient data of five single-centre observational studies to determine the effect of amantadine treatment among patients with ischaemic stroke, intracerebral haemorrhage, subarachnoid haemorrhage, community-acquired bacterial meningitis and status epilepticus, admitted between January 2012 and December 2015 and ventilated >= 7 days. Patient selection and multivariable regression modelling were used to adjust for differences in intergroup comparison and for parameters associated with consciousness. Improvement of consciousness 5 days after treatment initiation was defined as primary outcome. Secondary outcomes included Glasgow Coma Scale (GCS) at day 5 and GCS at day 10, rate of ICU delirium, epileptic seizures and all-cause mortality at 90 days. Results Overall, 84 of 294 (28.6%) eligible patients received amantadine. Amantadine treatment was associated with improvement of consciousness at day 5 (amantadine: 86.9% vs control: 54.0%; absolute difference: 32.9 (20.0-44.2); adjusted OR (aOR): 5.71 (2.50-13.05), p<0.001). Secondary outcomes showed differences in GCS 5 days (9 (8-11) vs 6 (3-9), p<0.001) and GCS 10 days (10(8-11) vs 9(6-11),p=0.003) after treatment initiation. There were no significant differences regarding all-cause mortality (aOR: 0.89 (0.44-1.82), p=0.758) and ICU delirium (aOR: 1.39 (0.58-3.31), p=0.462). Rate of epileptic seizures after initiation of amantadine treatment was numerically higher in the amantadine group (amantadine: 10.7% vs control: 3.0%; absolute difference: 7.7 (0.3-16.4); aOR: 3.68 (0.86-15.71), p=0.079). Conclusions Amantadine treatment is associated with improved consciousness among patients with different types of non-traumatic brain injury in this observational cohort analysis. Epileptic seizures should be considered as potential side effects and randomised controlled trials are needed to confirm these findings.
CRIS-Team WoS Importer:2022-02-11